(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This study aims to determine the factors that determine BKB Nurul Fikri in choosing digital marketing to increase the number of consumers, how to implement and the implications of digital marketing to increase the number of consumers of the Nurul Fikri Learning Guidance and Consultation Institute (BKB NF). This study uses a qualitative method because the researcher wants to get something objective by getting direct sources from the head of the branch, the head of the marketing department, tutors and students. The data collected by interview, observation and direct documentation at BKB Nurul Fikri Surakarta. The results of this study showed that the factors determined Nurul Fikri BKB in choosing digital media were to expand information, create awareness, perception, and improve service. BKB Nurul fikri has been using digital media websites and social media (youtube, Instagram and Facebook) for 7 years. The implication of using digital marketing is the increasing of quality and quantity. The increasing of quality can be showed from the Human Resource and servise while the increasing of quantity can be showed from the number of registration.